Fluoride toothpastes containing micrometric or nano-sized sodium trimetaphosphate reduce enamel erosion in vitro - Danelon, Marcelle [UNESP]; Pessan, Juliano Pelim [UNESP]; Santos, Vinicius Rodrigues dos [UNESP]; Chiba, Erika Kiyoko [UNESP]; Garcia, Luhana Santos Gonzales [UNESP]; de Camargo, Emerson Rodrigues; Delbem, Alberto Carlos Botazzo [UNESP] (MJS Publishing, Medical Journals Sweden AB, 2018)
Objective: To evaluate the effect of fluoride toothpastes supplemented with micrometric or nano-sized sodium trimetaphosphate (TMP or TMPnano, respectively) on enamel erosion in vitro, as well as the influence of salivary acquired pellicle and saliva. Material and methods: Bovine enamel blocks (n = 120) were randomly assigned into the following experimental toothpastes: no F/TMP/TMPnano (Placebo); 1100 ppm F (1100 ppm F); 1100 ppm F plus 3% TMP or 3% TMPnano (1100 TMP or 1100 TMPnano, respectively) and 5000 ppm F (5000 ppm F). Erosive challenge was performed by immersion of the blocks in citric acid for 5 min, followed by 2 h immersion in human or artificial saliva, 4×/day, during 5 days. After each erosive challenge, blocks were exposed to slurries of the toothpastes. Enamel erosion (µm), surface hardness (SHf) and cross-sectional hardness (ΔKHN) were analyzed as response variables and the data were submitted to two-way ANOVA, followed by the Student–Newman–Keuls test (p <.05). Results: 1100 TMPnano significantly reduced enamel loss when compared to 1100 TMP (p =.002), reaching values similar to those promoted by 5000 ppm F (p =.96). 1100 ppm F presented significantly lower enamel loss than Placebo (p <.001), and higher than 1100 TMP (p <.001). Significantly higher SHf and lower ΔKHN was observed for 1100 TMPnano and 5000 ppm F when compared with the other groups (p <.001). The type of saliva did not influence enamel erosion, SHf and ΔKHN for the groups treated with TMP-containing toothpastes. Conclusion: The addition of 3% TMPnano to 1100 ppm F toothpastes significantly increases the protective effect against enamel erosion in vitro when compared with its counterparts with micrometric TMP or without TMP. This effect was not influenced by the presence of acquired enamel pellicle and saliva.
Keywords: nano-size; tooth erosion; Toothpastes